Investigação do papel da calicreína 8 em câncer de cabeça e pescoço - Stefanini, Ana Carolina Buzzo (2014)
Introduction - The head and neck squamous cell carcinomas (HNSCCs) are among the most frequent types of cancer, with more than 600,000 new cases per year worldwide. The five-year survival rate is low in this disease and one of the reasons is that patients with tumours in early stages frequently exhibit few symptoms, resulting in diagnosis delay and severe morbidity. The understanding of the molecular pathways involved in the initiation and progression of these tumors is therefore important not only for understanding their biology, but also for the development of more effective preventive and therapeutic approaches. In previous studies of our group, the kallikrein 8 gene (KLK8) was observed differentially expressed in laryngeal carcinomas and its surgical margins, which highlights its potential as a tumor marker, similar to another member of KLK family, kallikrein 3 or PSA. Objectives and Methodology - The overall objective of the present study was to investigate the participation of the kallikrein 8 in the HNSCC development. The specific objectives included (a) to investigate the phylogenetic relationships among KLKs genes using the MEGA program, (b) to analyze, by real time PCR, the expression pattern of the KLK8 gene and its most abundant isoform in HNSCC and their surgical margins, (c) to evaluate the effect of elevated expression of KLK8 in HNSCC secretome, using conditioned medium and proteomic and metabolomic approaches, (d) to develop molecular homology modeling of protein hK8 by bioinformatics tools. Results - The phylogenetic analysis of human kallikrein genes and their isoforms confirmed the idea that these genes evolved from a single common ancestor by successive tandem duplications and chromosomal rearrangements facilitated by repetitive elements. The results of gene expression analysis in tumor tissues showed that the variant 1 of KLK8 has significantly reduced levels in HNSCC, unlike the other five variables. The ectopic expression of this variant resulted in changes of cell morphology, increased proliferation, viability and migratory capacity, but no alterations in invasiveness. The data from cells with ectopic expression of KLK8 revealed small differences in their proteomes compared to control cells. Otherwise, these cells exhibited changes in their glycolytic pattern and in the effect of their secretome on the metabolism of other cells. Conclusion - This study was important to answer some questions and raise others questions about the role of KLK8 gene in carcinomas of the head and neck. For the first time, differences in expression of KLK8 isoforms were observed in HNSCC and the effects of ectopic KLK8 expression on the proteome and the secretome of HNSCC cells.